PENGARUH FILANTROPI, CASH HOLDING DAN FAKTOR LAINNYA TERHADAP NILAI PERUSAHAAN - Bela Meilinda Phangestu; Frestin Chrisnanti (E-Jurnal Akuntansi TSM, 2022)
The purpose of this research is to provide empirical evidence about the impact of philanthropy, cash holding, board of directors size, return on assets, dividend payout ratio, debt to assets ratio, and firm size on firm value. The object observed in this research is nonfinancial companies that were listed on the Indonesian Stock Exchange during the period from 2017 to 2020. The sampling method used was the purposive sampling method. There were 59 nonfinancial companies obtained from sampling and then analyzed using multiple regression analysis on the SPSS application. The results of research that has been conducted reveal that philanthropy, return on assets, and firm size influence firm value whereas cash holding, board of directors size, dividend payout ratio, and debt to assets ratio do not influence firm value.Firm value